The Effect of Exercise on Elderly Body Balance which Measured By Romberg Test Study in Plamongansari Pedurungan Semarang - Annafisah, Zuhaida; Rosdiana, Ika (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: Balance disorders is a major cause which often lead elders to fall easily. Body balance reduction of elders can be helped by many variety of balance exercises, one of them is elders exercise. There have been many researches on the assessment of body balance. But a research carrying a Romberg Test to assesses static balance by closing and opening eyes as a visual organ has not been done. This study aims to determine the effect of exercise on elderly body balance which measured by Romberg Test.Design and Method: Analytic observational research with cross-sectional approach was conducted to elderly who routinely do exercises and to them who don’t. There were 82 samples, consisted of 41 elderly do exercises and 42 elderly who don’t. Body balances of both groups were measured using the Romberg test. The data were analyzed by chi-square.Result: Among the 41 elderly who do exercise, consisted of 12 men and 29 women, showed 97.56% balanced and 2.44% unbalanced. While 41 elderly aged over 60 years who don’t do exercise, consisted of 15 men and 26 women, showed 46.34% balanced and 53.66% unbalanced. The results of chi-square test showed p = 0.000; r = 0.495.Conclusion: The elderly exercises influence the body balance as measured using the Romberg Test to healthy elderly, with a moderate degree of correlation (Sains Medika, 4(2):142-146).